2022
DOI: 10.3389/fnut.2022.865077
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Screening of Hypoglycemic Activity of Total Ginsenosides GBE-5 Fraction From Panax Ginseng Berry Based on UHPLC–MS Metabolomics

Abstract: ObjectiveGinseng berry (GB) was the mature fruit of medicinal and edible herb, Panax ginseng C.A. Meyer, with significant hypoglycemic effect. Ginsenoside was the main hypoglycemic active component of GB. Evaluating and screening the effective components of GB was of great significance to further develop its hypoglycemic effect.MethodsThe polar fractions of ginseng berry extract (GBE) were separated by a solvent extraction, and identified by ultra-high performance liquid chromatography–high-resolution mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Ginsenoside is the main hypoglycemic active component of GB. Heyu Ginsenoside extract 5 (GBE-5) has a more significant hypoglycemic effect than other extract components [ 77 ]. Using the kyoto encyclopedia of genes and genomes (KEGG) metabolic pathway enrichment analysis, it is found that ferroptosis may be one of the potential metabolic pathways for GBE-5 components to exert hypoglycemic regulation [ 77 ].…”
Section: Chinese Herbal Medicine or Herbal Natural Compounds In Impro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenoside is the main hypoglycemic active component of GB. Heyu Ginsenoside extract 5 (GBE-5) has a more significant hypoglycemic effect than other extract components [ 77 ]. Using the kyoto encyclopedia of genes and genomes (KEGG) metabolic pathway enrichment analysis, it is found that ferroptosis may be one of the potential metabolic pathways for GBE-5 components to exert hypoglycemic regulation [ 77 ].…”
Section: Chinese Herbal Medicine or Herbal Natural Compounds In Impro...mentioning
confidence: 99%
“…Heyu Ginsenoside extract 5 (GBE-5) has a more significant hypoglycemic effect than other extract components [ 77 ]. Using the kyoto encyclopedia of genes and genomes (KEGG) metabolic pathway enrichment analysis, it is found that ferroptosis may be one of the potential metabolic pathways for GBE-5 components to exert hypoglycemic regulation [ 77 ]. Moreover, cryptochlorogenic acid (CCA) is an active compound in mulberry leaves, and CCA could inhibit ferroptosis by activating cystine/glutamate transporter (XC-)/GPX4/Nrf2 and inhibiting NCOA4 in diabetes, thereby reducing islet injury in the diabetic model [ 78 ].…”
Section: Chinese Herbal Medicine or Herbal Natural Compounds In Impro...mentioning
confidence: 99%
“…Ginsenoside, the active ingredient in traditional Chinese medicine ginseng, has anticancer, antioxidant, anti-inflammatory, immunomodulatory, hypoglycemic, and antidiabetic effects. Wang et al found that ginsenoside GBE-5 could be involved in lipid metabolism, biosynthesis of unsaturated fatty acids, and regulation of ferroptosis by UHPLC–MS metabolomics [ 99 ]. In addition, salidroside is a phenolic compound that was obtained from the Chinese herb Rhodiola and was known to have antioxidant, antiaging, anti-inflammatory, free radical scavenging, enhanced abnormal lipid metabolism, reduced iron accumulation, inhibited ferroptosis, and heart and blood vessel protection properties [ 100 102 ].…”
Section: Effects Of Ferroptosis On Cardiovascular Diseasementioning
confidence: 99%